Preparation of flame-retardant HDPE composites with synergistic strategy by the combination of phosphorus-containing modifier and magnesium oxychloride cement. (September 2022) - Song, Yanjiang; Xu, Liyan; Ye, Feixiang; Wen, Bianying; Qi, Panpan; Yang, Haitang
Highlights: Improving greatly the flame-retardant performance of the HDPE composites by the multi-stage decomposition endothermic and thermal expansion effects of MOC. Good synergistic flame-retardant effect of phosphoric acid was obvious on HDPE/MOC composites. Decreased peak heat release rate, total smoke production and fire growth index of composites by adding the phosphorus containing titanate coupling agent. The heat release per unit mass of PE and the mass residue rate per unit mass of PE are introduced to analyze the quantitative synergistic flame-retardant effect. Abstract: Magnesium oxychloride cement (MOC), as an inorganic gel material with 5Mg(OH)2 ·MgCl2 ·8H2 O as its main component, has higher heat absorption and water yield during thermal decomposition than that of magnesium hydroxide (MH). It can also be used in flame-retardant polymer materials like MH. The flame retardancy of HDPE/MOC composites increases with the addition of MOC. Compared with pure HDPE, when the MOC filling amount is 60 wt%, the total heat release and total smoke production decrease by 50.6% and 50.8% respectively, and the total heat release per mass for HDPE decreases from 53 kJ/g to 32.2 kJ/g. Phosphoric acid (PA) shows a good synergistic flame-retardant effect with MOC while improving the water resistance of MOC. After adding 1 wt% PA, the peak heat release rate and peak smoke production rate of HDPE/MOC/PA (50/49/1) decrease by 30% and 25.6% respectively, and the fire growth index (FGI) decreases by 24.6%. Phosphorus-containing coupling agent (isopropyl tri(dioctylpyrophosphate) titanate) can improve the size distribution of MOC, and also has synergistic flame-retardant effect with MOC in HDPE/MOC composites.